2016
DOI: 10.1016/j.engstruct.2015.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a simplified model for the design of a super-tall mega-braced frame-core tube building

Abstract: Abstract:Resilience-based earthquake design for next-generation super-tall buildings has become an important trend in earthquake engineering. Due to the complex structural system in super-tall buildings and the extreme computational workload produced when using refined finite element (FE) models to design such buildings, it is rather difficult to efficiently perform a comparison of different design schemes of super-tall buildings and to investigate the advantages and disadvantages of different designs. Here, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…With rapid urbanization and fast‐growing population, an increasing number of super high‐rise buildings with complex configurations and innovative structural systems have been built in megacities around the world . Although most of the skyscrapers are located in cities with low or moderate seismicity, such as Dubai, Shanghai, Shenzhen, and Hong Kong to name a few, recent studies revealed that long‐period ground motions from distant large‐magnitude earthquakes could cause great impact on the safety and functionality of high‐rise buildings .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With rapid urbanization and fast‐growing population, an increasing number of super high‐rise buildings with complex configurations and innovative structural systems have been built in megacities around the world . Although most of the skyscrapers are located in cities with low or moderate seismicity, such as Dubai, Shanghai, Shenzhen, and Hong Kong to name a few, recent studies revealed that long‐period ground motions from distant large‐magnitude earthquakes could cause great impact on the safety and functionality of high‐rise buildings .…”
Section: Introductionmentioning
confidence: 99%
“…The condensed building model inevitably neglects the details of the real building structure, such as the coupling beams in shear walls and the connections between the outrigger trusses and the mega columns. It is almost impossible for the condensed model to include these details, but they are often seismic vulnerable for super high‐rise buildings under long‐period ground motions . Thus, the condensed building model may not be adequate for the seismic assessment of high‐rise buildings under long‐period ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, the displacement components δ t and w can be easily derived from Equations (22) and (26).…”
Section: MXmentioning
confidence: 99%
“…Moreover, other simplified methods can be applied in cases where the vertical stiffening structures are constituted by frames [22,23], or by open shear walls [24]. In the literature there are also simplified methods for the dynamic analysis of tall buildings that involve the use of analytical [25,26] or FE models [27].…”
Section: Introductionmentioning
confidence: 99%
“…Li and Wu (2004), Poon et al (2011), Jiang et al(2014) and Lu et al (2011Lu et al ( , 2013Lu et al ( , 2014Lu et al ( , 2016 found that the outriggers could dissipate a great deal of the seismic energy after yielding, which would significantly influence the nonlinear seismic responses of buildings. Moehle (2015) indicated that the outriggers could be designed to yield and fail as "fuses" of the building, to dissipate the seismic energy and to protect the primary structure.…”
Section: Introductionmentioning
confidence: 99%